An comparison of acute toxicities and patient‐reported outcomes between intensity‐modulated proton therapy and volumetric‐modulated arc therapy after ipsilateral radiation for head and neck cancers. Issue 2 (3rd December 2021) - Jeans, Elizabeth B.; Shiraishi, Satomi; Manzar, Gohar; Morris, Lindsay K.; Amundson, Adam; McGee, Lisa A.; Rwigema, Jean‐Claude; Neben‐Wittich, Michelle; Routman, David M.; Ma, Daniel J.; Patel, Samir H.; Foote, Robert L.; et al.
Abstract: BACKGROUND: Intensity‐modulated proton therapy (IMPT) demonstrates superior dose distribution over volumetric‐modulated arc therapy (VMAT) for sparing organs‐at‐risk (OARs) in ipsilateral radiotherapy. To determine a clinical benefit, assessment of patient‐reported outcomes (PRO) and physician‐reported toxicities alongside a dosimetric analysis is needed. METHODS: Plans were analyzed for dosimetric differences. PROs were compared for patients undergoing ipsilateral curative‐intent radiotherapy for tonsil and salivary gland cancers with VMAT or IMPT from 2015 to 2020. Physician‐reported toxicities were compared. RESULTS: In 40 patients, IMPT was associated with decreased dose to multiple OARs and less deterioration in the following PROs: pain, swallowing function, dry mouth, sticky saliva, sensory change, cough, speech, feeling ill, and social eating. Physician‐reported toxicities demonstrated less oral pain. CONCLUSION: IMPT is associated with decreased dose to OARs and less patient‐reported acute deterioration in multiple head and neck domains. A strong consideration for IMPT in ipsilateral head and neck patients with cancer is warranted.